Do financial advisors have different beliefs than lay people? - Matthias Rumpf; Michael Haliassos; Tetyana Kosyakova; Thomas Otter (Goethe University Frankfurt, Institute for Monetary and Financial Stability (IMFS), 2024)
We conduct a web-based experiment in which we elicit the recommendations of professional and lay advisors on the risky portfolio share of randomly assigned vignettes of investors. Both professionals and lay advisors respond to investor characteristics broadly in agreement with portfolio theory, but they are also influenced by their own characteristics and portfolios. Professionals tend to respond more than lay advisors to investor characteristics, but also to their own risk aversion and income. Allowing for unobserved heterogeneity and estimating the distribution of advice through Bayesian methods, we find that professionals tend to recommend more limited risk exposure to older college educated groups compared to their peers, while they recommend young, lower-educated individuals to include more stocks than what their peers and elders would recommend.
Keywords: 330